INFLUENCE OF WEATHER FACTORS ON THE OCCURRENCE OF SPOTTED POD BORER (Maruca vitrata Geyer) ON GREENGRAM IN SUMMER - V. SRINIVASA RAO, C. SANDHYA RANI, G. RAMACHANDRA RAO, M.S.V. CHALAM, P. ANIL KUMAR and (The Journal of Research, PJTSAU, 2017)
Field experiment was conducted to study the seasonal occurrence of spotted pod borer, Maruca vitrata on greengram at Agricultural Research Station, Madhira, during summer 2009-10 & 2010-11. The results revealed that the initial incidence of M. vitrata was observed during 3rd week of March i.e. at the bud initiation stage of the crop. Peak bud infestation (16%) was noticed in 13th standard week. The pest infestation was gradually declined and reached minimum by the last week of April (17th Standard week) with 0.5 larvae & webs per plant and has disappeared. The results also revealed that all the abiotic factors have been found to exert significant influence and they together contributed the per cent variation in number of larvae per plant by 53.48%, 76.83 % in bud infestation, 73.85 % in flower infestation, 84.61% in number of webs per plant and 55.05 % in pod damage by M. vitrata. Maximum temperature has been found to exert significant negative influence on larval incidence & bud infestation whereas minimum temperature found to exert significant positive influence on larval incidence, flower infestation and webbing. Evening relative humidity exert significant negative influence on larval incidence. All the weather variables have been found to exert positive influence on pod damage but non-significant in summer season.